Mapping Tonal Hierarchy in the Brain. (15th June 2021) - Sauvé, Sarah A.; Cho, Alex; Zendel, Benjamin Rich
Highlights: N1, P2 and ERAN are modulated by scale degree during passive listening. N1, P2 and ERAN are correlated with pitch height and goodness-of-fit ratings. The magnitude of these correlations is similar, explaining variation equally. Individual differences carry the most explanatory power. Abstract: In Western tonal music, pitches are organized hierarchically based on their perceived fit in a specific tonal context. This hierarchy forms scales that are commonly used in Western tonal music. The hierarchical nature of tonal structure is well established behaviourally; however, the neural underpinnings are largely unknown. In this study, EEG data and goodness-of-fit ratings were collected from 34 participants who listened to an arpeggio followed by a probe tone, where the probe tone could be any chromatic scale degree and the context any of the major keys. Goodness-of-fit ratings corresponded to the classic tonal hierarchy. N1, P2 and the Early Right Anterior Negativity (ERAN) were significantly modulated by scale degree. Furthermore, neural marker amplitudes and latencies were significantly correlated with similar magnitude to both pitch height and goodness-of-fit ratings. This is different from the clearer divide between pitch height correlating with early neural markers (100–200 ms) and tonal hierarchy correlating with late neural markers (200–1000 ms) reported by Sankaran et al. (2020) and Quiroga-Martinez et al. (2019). Finally, individual differences were greater than any main effects detected when pooling participants and brain-behavior correlations vary widely (i.e. r  = −0.8 to 0.8).